POTENSI UBI JALAR PUTIH (Ipomoea batatas linneaus varietas) SEBAGAI MEDIA ALTERNATIF PERTUMBUHAN BAKTERI Staphylococcus aureus - Siti Juariah (Jurnal Penelitian Farmasi Indonesia, 2021)
Bacterial growth is highly dependent on nutrient sources, energy sources and environmental conditions. Nutrien agar is a medium that is often used for bacterial growth. The use of Nutrien agar requires a high cost, so it is considered to have no economic value. The use of alternative media is cheap, easy to obtain, and has a large source of nutrients for the growth of the required bacteria. White sweet potato (Ipomoea batatas linneaus variety) has a high carbohydrate content to be used as a carbon source for bacterial growth. The purpose of this study was to reveal the potential of white sweet potato (Ipomoea batatas linneaus variety) as an alternative medium for the growth of Staphylococcus aureus bacteria. This research uses experimental laboratory methods. Staphylococcus aureus growth was observed, and total plate number was calculated on nutrien agar and white sweet potato (Ipomoea batatas linneaus varieties) media. Based on the research results, Nutrien agar is small in size, from 0.1 cm to a yellow colour and round shape. In comparison, the white sweet potato (Ipomoea batatas linneaus variety) has a small size of 0.1 cm, milky white with a round shape. The results of the calculation of the otal plate number from the Nutrien agar medium was 1.6 X (104) CFU. In comparison, the total plate number from the white sweet potato (Ipomoea batatas linneaus variety) medium was 8.9 X (104) CFU. From the results of this study, it can be concluded that white sweet potato (Ipomoea batatas linneaus variety) can be used as an alternative medium for the growth of Staphylococcus aureus bacteria.